THE PHILOSOPHICAL BASIS OF CRITICAL DISCOURSE ANALYSIS - Erni Dewi Riyanti (Sekolah Tinggi Agama Islam Sadra, 2023)
Critical discourse analysis has become an effective multidisciplinary approach to uncovering hidden ideologies and powers along with the changing times and the increasing prevalence of various discourses in society, both in the form of information written in text and distributed in the digital world. Discourse battles are commonplace in the context of life—as a form of dialectics and freedom to convey ideas. Researchers through this article discuss basic assumptions about the basic or main principles of critical discourse analysis developed by Norman Fairclough and Ruth Wodak. The basic assumptions are that critical discourse analysis focuses on social issues, power relations are discursive, discourse shapes society and culture, discourse manages ideological works, discourse is historical, the relationship between text and society is mediated (discourse), discourse analysis is interpretive and explanatory, and discourse is a form of social action. The article also discusses three models of discourse analysis: the Sociocultural (Norman Fairclough), Socio-cognitive (Teun A. van Dijk), and Historical-Discourse (Ruth Wodak) models. Fairclough’s sociocultural model interprets text not only through the way objects are described but also through the relationships between objects that are defined. Meanwhile, Teun A. van Dijk’s socio-cognitive model emphasizes text, social cognition, and social context, forming a chain of analysis. Lastly, Ruth Wodak’s historical-discourse model puts historical aspects of discourse into his analysis.